Studi Eksplorasi Penerapan Permainan Vaccine Making Competition terhadap Kemampuan Spasial Siswa Kelas VIII - Nasrullah; Bernard; Zulfiana (Faculty of Tarbiyah and Teacher Training, 2024)
This research aims to explore the application of the Vaccine Making Competition game in developing the spatial abilities of class VIII students at SMP Negeri 4 Majauleng. The research type applied was pre-experimental, involving 17 students as research samples. The data analysis technique used is descriptive statistics, which is equipped with normalized gain value calculations. The research results show that the application of the Vaccine Making Competition game provides positive changes to students' spatial abilities. Descriptively, the initial quantitative achievements show an increase in spatial abilities (normalized gain) after being taught using the Vaccine Making Competition game in the medium category). Apart from that, students' responses to the Vaccine Making Competition game were very positive. The application of learning media to support student learning outcomes, such as spatial abilities, is an effort to increase their participation in planned activities. Through activities, a learning experience with media helps students construct the knowledge gained and each activity presented.